2017
DOI: 10.1016/j.jsat.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Addiction consultation services – Linking hospitalized patients to outpatient addiction treatment

Abstract: Background Approximately 15% of hospitalized patients have an active substance use disorder (SUD). Starting treatment for SUD, including medications, during acute hospitalizations can engage patients in addiction care. In July 2015, the Boston Medical Center Addiction Consult Service (ACS), began providing inpatient diagnostic, management, and discharge linkage consultations. We describe this implementation. Methods The ACS staff recorded SUDs diagnoses and medication recommendations and tracked follow-up da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
161
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 188 publications
(165 citation statements)
references
References 31 publications
1
161
3
Order By: Relevance
“…However, researchers that conducted that study also reported opioid prescribing did not change after patients received an OUD diagnosis (although researchers were not able to examine which clinicians provided the prescriptions before or after the OUD diagnosis) (Paulozzi et al, 2016). Programs to treat substance abuse disorders among inpatients have demonstrated success, although patients are often discharged without specific plans for treatment services and patient follow-up for post-discharge treatment is low (Naeger, Mutter, Ali, Mark, & Hughey, 2016; Rosenthal, Karchmer, Theisen-Toupal, Castillo, & Rowley, 2016; Trowbridge et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…However, researchers that conducted that study also reported opioid prescribing did not change after patients received an OUD diagnosis (although researchers were not able to examine which clinicians provided the prescriptions before or after the OUD diagnosis) (Paulozzi et al, 2016). Programs to treat substance abuse disorders among inpatients have demonstrated success, although patients are often discharged without specific plans for treatment services and patient follow-up for post-discharge treatment is low (Naeger, Mutter, Ali, Mark, & Hughey, 2016; Rosenthal, Karchmer, Theisen-Toupal, Castillo, & Rowley, 2016; Trowbridge et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have shown that histories of incarceration and homelessness are additional risk factors for higher rates of resistant infections 15–17 . Successful treatment of infections in this population is further complicated by a lack of concurrent inpatient treatment for substance use disorder, which very few hospitals currently offer 18–20 . Clinicians at many institutions remain apprehensive about the use of OPAT in this population.…”
Section: Specific Populations With Barriers To Traditional Transitionmentioning
confidence: 99%
“…Retention in care indicated that patients were receiving treatment for SUD. Previous studies have reported retention rates between 30 and 40% [20,21]. Given the short period of study, the retention rate was expected to be higher since attrition occurs over time [20,21] and patients who were discharged to another medical provider were still considered retained in care.…”
Section: Study Aimmentioning
confidence: 99%
“…Previous studies have reported retention rates between 30 and 40% [20,21]. Given the short period of study, the retention rate was expected to be higher since attrition occurs over time [20,21] and patients who were discharged to another medical provider were still considered retained in care. A reduction of substance use was considered a successful outcome since decreased substance use is correlated with less severe substance use disorder [22].…”
Section: Study Aimmentioning
confidence: 99%